2009
DOI: 10.3389/neuro.07.016.2009
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal activity predicts monkeys' decisions during an auditory category task

Abstract: The neural correlates that relate auditory categorization to aspects of goal-directed behavior, such as decision-making, are not well understood. Since the prefrontal cortex (PFC) plays an important role in executive function and the categorization of auditory objects, we hypothesized that neural activity in the PFC should predict an animal's behavioral reports (decisions) during a category task. To test this hypothesis, we tested PFC activity that was recorded while monkeys categorized human spoken words (Rus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 88 publications
4
44
2
Order By: Relevance
“…This suggests that a hierarchical relationship exists between STG and the vPFC whereby STG provides the "sensory evidence" to form the decision and vPFC activity encodes the output of the decision process. This hierarchical relationship is consistent with the STG's role as a part of functional circuit involved in the coding, representation, and perception of the nonspatial features of an auditory stimulus (i.e., auditory identity) (Cohen et al 2009(Cohen et al , 2007Rauschecker 1998;Rauschecker and Scott 2009;Rauschecker and Tian 2000;Romanski and Averbeck 2009;Romanski et al 1999b;Russ et al 2008a,b). This relationship may also be somewhat analogous to that observed in visual decision making: neural activity in parts of extrastriate visual cortex is highly sensitive to features of the visual stimulus and only weakly related to choice, whereas neural activity in area LIP of the parietal cortex, parts of the PFC, including the frontal eye fields, encode the input to, dynamics of, and output of the decision process, including an accumulation of evidence into a decision variable that governs the behavioral response (Britten et al 1992;Celebrini and Newsome 1995;Horwitz and Newsome 1999;Kim and Shadlen 1999;Newsome and Pare 1988;Roitman and Shadlen 2002;Salzman et al 1990Salzman et al , 1992Shadlen and Newsome 2001).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…This suggests that a hierarchical relationship exists between STG and the vPFC whereby STG provides the "sensory evidence" to form the decision and vPFC activity encodes the output of the decision process. This hierarchical relationship is consistent with the STG's role as a part of functional circuit involved in the coding, representation, and perception of the nonspatial features of an auditory stimulus (i.e., auditory identity) (Cohen et al 2009(Cohen et al , 2007Rauschecker 1998;Rauschecker and Scott 2009;Rauschecker and Tian 2000;Romanski and Averbeck 2009;Romanski et al 1999b;Russ et al 2008a,b). This relationship may also be somewhat analogous to that observed in visual decision making: neural activity in parts of extrastriate visual cortex is highly sensitive to features of the visual stimulus and only weakly related to choice, whereas neural activity in area LIP of the parietal cortex, parts of the PFC, including the frontal eye fields, encode the input to, dynamics of, and output of the decision process, including an accumulation of evidence into a decision variable that governs the behavioral response (Britten et al 1992;Celebrini and Newsome 1995;Horwitz and Newsome 1999;Kim and Shadlen 1999;Newsome and Pare 1988;Roitman and Shadlen 2002;Salzman et al 1990Salzman et al , 1992Shadlen and Newsome 2001).…”
Section: Discussionmentioning
confidence: 59%
“…We targeted the region of the STG that, based on MRI coordinates, coincides with the anterolateral belt of the auditory cortex; the anterolateral belt is part of the ventral auditory stream and consequently processes information about auditory identity (Rauschecker and Scott 2009;Rauschecker and Tian 2000). Since this task design is analogous to our previous study that demonstrated a role for the vPFC in decision making (Lee et al 2009;Russ et al 2008b), we can compare the current findings with those from our vPFC study to infer the functional and hierarchical computations that occur along the ventral pathway.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of low-level auditory features, these neurons seem to Single cell activity was usually recorded in BA 45A and BA 9/46v, both located rostrally to BA 8Av below the principal sulcus. Color-coded dots refer to the following studies: (Gifford et al, 2005), Romanski et al, 2005), (Cohen et al, 2007Russ et al, 2008a), (Romanski and Goldman-Rakic, 2002), (Cohen et al, 2006), (Lee et al, 2009;Russ et al, 2008b), (Sugihara et al, 2006), and (Gil-da-Costa et al, 2006) for activity in the vPM. Abbreviations: as arcuate sulcus, cs central sulcus, ipd inferior precentral dimple, ls lateral sulcus, ps principal sulcus, vpm ventral premotor area.…”
Section: Origins Of the Ifc Sensitivity To Vocal Intonationsmentioning
confidence: 99%
“…vlPFC neurons are strongly modulated by monkeys' choices (Russ et al 2008;Lee et al 2009). Neural activity in the inferior frontal lobe of the human cortex is also modulated by choice when listeners judge the content of ambiguous speech sounds (Binder et al 2004).…”
Section: Neural Correlates Of Auditory Perception Along the Ventral Amentioning
confidence: 99%